The effects of financial leverage on firm performance in shariah-listed consumer products & services firms / Masturah Ma'in ... [et al.] - Ma'in, Masturah; Keshminder, J.S; huah, S.C; Ahmad Afindi, Khairol Syafiqah (Accounting Research Institute (ARI), 2022)
This study examined the effects of financial leverage on firm performance that focussed on Shariah-listed Consumer Products & Services firms in Malaysia from 2014 to 2018. The data for firm performance was Tobin's Q and return on asset, while debt-asset ratio, debt-equity ratio, and tangibility were indicators of financial leverage. This study applied a balanced panel regression model, including the pooled regression model, fixed-effect model, and random effect model. The results indicated that Tobin's Q is the best model to identify the impact of financial leverage on Shariah firm performance. The outcome showed that the financial leverage indicators had a significant and negative effect on Shariah firm's performance, in line with the assumption of the pecking order theory assumptions that internal financing will be the first option of financing compared to external financing.